Can modern input use be promoted without subsidies?: An analysis of fertilizer in Ethiopia - Rashid, Shahidur; Tefera, Nigussie; Minot, Nicholas; Ayele, Gezahegn (Wiley, 2013)
Fertilizer use in Ethiopia has nearly quintupled since official elimination of direct input subsidies in the early 1990s. During this time, policies changed from liberalization, with both private and public sector participation, to a government monopoly over imports along with exclusive marketing through farmers’ cooperatives. This article presents estimates of detail costs and margins in the value chain, econometrically derived profitability and yield responses, as well as costs of the government's fertilizer promotion policies. Results suggest that (a) irrespective of the methods of calculation, fertilizer use in major cereal is profitable; (b) while there is no official subsidy program, fertilizer promotion has involved large fiscal costs—estimated at US$40 million per year since 2008; and (c) there has been a mismatch between government's policy targets and the effective fertilizer demand, resulting in large carryover stock with estimated implicit costs of US$30 million per year during 2008–2011. Areas of policy attention, value chain improvements, and ongoing efforts to improve for fertilizer use and profitability are discussed.